The Effect of Institutional Ownership, Company Size, Profitability on Debt Policy in Health Sector Companies - Citra Parsi; Atikah Sitorus; Nurmala Lubis; Claudia Silitonga; An Azzahra (Journal of Indonesian Management, 2024)
This study looks at how debt policy in health sector companies listed on the Indonesia Stock Exchange (IDX) is influenced by institutional ownership, company size, and profitability. Data was collected through a quantitative approach from annual financial reports for the years 2019-2023. After considering outlier data, the study population consisted of 34 businesses, which resulted in 31 observations through purposive sampling method. The analysis was conducted with classical assumption tests and multiple linear regression using the SPSS software program. The results show that firm size has no significant effect on debt policy, but institutional ownership and profitability have a significant effect. The model is free from heteroscedasticity, normality, and multicollinearity problems thanks to the classical assumption test. According to the regression analysis, the model can explain 62.1% of the variation in debt policy. The study found that, although more profitable firms tend to rely on internal funding sources, institutional ownership can serve as a monitoring tool. However, firm size is not a major factor in debt policy making. This study provides practical implications for corporate financial management in the healthcare industry and helps investors assess the factors that influence corporate funding structure. It is expected that future research will analyze more variables due to research limitations, such as the small sample size and relatively short research time.